Correction: Generality of toxins in defensive symbiosis: Ribosome-inactivating proteins and defense against parasitic wasps in Drosophila. - Matthew J Ballinger; Steve J Perlman (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1006431.].